PACE: A group randomised controlled trial to increase children's break-time playground physical activity. Issue 5 (May 2016) - Parrish, Anne-Maree; Okely, Anthony D.; Batterham, Marijka; Cliff, Dylan; Magee, Christopher
Abstract: Objectives: To assess the effect of a school playground intervention on the physical activity levels of primary/elementary aged children. Design: Two-arm parallel group randomized controlled trial. Methods: In 2011, children aged 4–13 years from thirteen primary/elementary schools (in Illawarra, New South Wales, Australia) were invited to participate in the study. School recruitment was based on existing policies, equipment and willingness to participate. Participating schools were randomly allocated to the intervention or control using the 'hat and draw' method. The intervention was delivered over four months. Intervention schools introduced policy changes and portable equipment to break-time after baseline measures were collected. The primary outcome was the proportion of break-time spent in Moderate to Vigorous Physical Activity (MVPA) assessed by the System for Observing Playground Activity in Youth (SOPLAY). The analysis involved linear mixed models adjusting for the clustering effect of schools. The study is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12614001128684). Results: Four schools (two intervention and two control) met the inclusion criteria (1582 children: 790 males; 267 controls, total of 792 females; 248 controls). Students from the intervention schools had a greater increase at follow-up in the proportion of break-time in MVPA; (adjusted difference = 12.5 percentage points, 95% CI [−13.0%, 38.0%]; P  = 0.17; r  = 0.6) compared to the controls. MVPA at recess significantly increased (adjusted difference = 18.0 percentage points, 95% CI [6.9%, 29.1%]; P  = 0.02; effect size = 0.7). There were no significant increases in MVPA when examining overall break times. Results were greater for girls compared to boys. Conclusions: Making environmental and policy changes are promising strategies for promoting health-enhancing physical activity during school break-time.